AN INTEGRATED APPROACH TO THE SELECTION OF EMBRYOS USING AUXILIARY REPRODUCTIVE TECHNOLOGIES IN INCREASING THE EFFECTIVENESS OF FETAL RESULTS - Suraya Z. Yuldasheva; Yulduz G. Rasul-Zade (Central Asian Journal of Medicine, 2023)
Cryopreservation of gametes and embryos is one of the most pressing problems of modern reproductive medicine. A comparative analysis of the effectiveness of the use of natural and frozen materials was carried out in the embryological laboratory. With the help of carriers of the closed (n = 598) and open (n = 665) types, 1263 molten embryos were transferred. Most of the indicators were good when using open carriers. The data obtained allows us to conclude that vitrification of morphologically normal gametes does not reduce the effectiveness of cryodastures and maintains their reproductive status. The use of open-type carriers to vitrify and store embryos demonstrates high levels of embryo retention after cryoconservation, with rates of miscarriage and low loss. It is assumed that this is due to the direct contact of the biological object (embryo) with liquid nitrogen and high freezing levels, which can be a decisive factor in the successful determination of vitrification in open carriers.